Accident rate of regional railway vehicles at railway crossings for the years 2014 to 2018 - Jakub Seidl (Acta Polytechnica CTU Proceedings, 2022)
From a societal point of view, there are growing demands to increase traffic safety and reduce the risk of accidents of rail and road vehicles. The research to increase the safety of railway vehicles, which is carried out at the Faculty of Mechanical Engineering of the Czech Technical University in Prague, aims to increase the active and passive safety of railway vehicles. Components and systems of active safety are designed to reduce the risk of an accident. Components and systems of passive safety are designed to minimize the consequences of accidents. One of the parts of the active safety of railway vehicles is the condition and safety of the railway lines on which the railway vehicle is operated. The first part of the article focuses on the evaluation of accident statistics of railway vehicles with other road users at railway crossings for the years 2014 to 2018 with regard to the cause of the accident and the level of security of railway crossings. The conclusion of the article is devoted to proposals for solutions that could lead to a reduction in accidents at railway crossings.